Demystifying Wealth Disparity Pattern in India : An Approach Through Decennial Debt Investment Data - Singh, Shashank Shekhar (Arthshastra Indian Journal of Economics & Research, 2020)
This paper provided insights in wealth disparity among the rural and urban population in India. The data showed that disparity is prevalent not only in physical assets, but also in financial assets. This disparity is homogeneously present across geographies, that is, rural and urban India. The data available was found to be skewed, and distribution was non-normal. It was observed that shares and debentures owned by urban households were much higher than their rural counterparts as on 31.06.2012. Similarly, in cases of other classes of financial assets, mean value for urban population was higher, which clearly indicated that the investment in financial assets was lower in rural population.